Assistance et santé publique dans la construction de l'État moderne : l'expérience portugaise - Abreu, Laurinda (2015)
Over the past three decades, knowledge on the process of early modern state building has increased,covering new geographical areas and developing new topics, including the ideological dimensions of court ceremonies and other cultural and symbolic elements. Focused on Portugal, this paper aims to look upon poor relief and public health as important fi elds for political assertion, consolidation and investment of royal power. Based on strong empirical evidence, it will demonstrate that the 16th century Portuguese Crown was able to establish and implement homogenous and centralized poor relief and health care policies and regulations for social and political purposes. It will include the creation of two nationwide networks, among other aspects : one comprising royal confraternities, the Misericórdia confraternities, to whom the Crown gave quasi-monopoly over formal poor relief, including hospital administration, and the other, formed by doctors, apothecaries and surgeons, appointed by the central government to serve the poor. Together, the Misericórdias and the “medical net” gave the Crown the opportunity to intervene in the daily life of communities, increasing its capacity to mobilize the local elite to participate in royal initiatives. The gradual structuring and implementation of the Portuguese poor relief and health care “system” reflects not only a specific exercise of sovereign powers but also a deliberate use of this system as an instrument for state formation.